1991
DOI: 10.1007/bf01964408
|View full text |Cite
|
Sign up to set email alerts
|

Role of gamma interferon inToxoplasma gondii infection

Abstract: Toxoplasma gondii has emerged as an important pathogen in the ever increasing numbers of patients with disorders of the immune system. Better understanding of the mechanisms of resistance of the host against this protozoan is important for development of safe, effective alternative treatment regimens for toxoplasmosis. Gamma interferon is the cytokine that plays a central role in protection against Toxoplasma gondii. The purpose of this review is to highlight the current knowledge of the role of gamma interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 76 publications
(43 reference statements)
0
18
0
2
Order By: Relevance
“…There is abundant evidence that IFN-␥ is the major cytokine involved in activation of macrophages and neutrophils to a candidacidal stage (3,9). The administration of IFN-␥ to mice beneficially influences the course of experimental infection with various pathogens, such as Toxoplasma gondii (32), Leishmania major (17), Trypanosoma cruzi (6), and Pneumocystis murina (30). In most models, macrophages and/or neutrophils are the main effector cells of IFN-␥-stimulated microbicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant evidence that IFN-␥ is the major cytokine involved in activation of macrophages and neutrophils to a candidacidal stage (3,9). The administration of IFN-␥ to mice beneficially influences the course of experimental infection with various pathogens, such as Toxoplasma gondii (32), Leishmania major (17), Trypanosoma cruzi (6), and Pneumocystis murina (30). In most models, macrophages and/or neutrophils are the main effector cells of IFN-␥-stimulated microbicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that T cells play a major role in mediating protective immunity against low-and high-virulence strains of T. gondii from studies that depleted T cells in vivo with a mAb against Thyl.2 (11). Further evidence comes from the finding that interferon y released from sensitized T cells acts as a major mediator of the host defenses against T. gondii infection (19,20). Taking these results together, one might suggest that the expression of HSPs in mice immunized by Toxoplasma cell homogenates may be attributable to cytok-ines like interferon y.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon γ is clearly important in the control of infection. INFγ knockout mice cannot control infection and anti-INFγ can cause reactivation encephalitis in chronically infected mice (1,19,20).…”
Section: Introductionmentioning
confidence: 99%